Bioequivalence of inhaled drugs: fundamentals, challenges and perspectives. (March 2013) - Apiou-Sbirlea, Gabriela; Newman, Steve; Fleming, John; Siekmeier, Ruediger; Ehrmann, Stephan; Scheuch, Gerhard; Hochhaus, Guenther; Hickey, Anthony
Interest in bioequivalence (BE) of inhaled drugs derives largely from the desire to offer generic substitutes to successful drug products. The complexity of aerosol dosage forms renders them difficult to mimic and raises questions regarding definitions of similarities and those properties that must be controlled to guarantee both the quality and the efficacy of the product. Despite a high level of enthusiasm to identify and control desirable properties there is no clear guidance, regulatory or scientific, for the variety of aerosol dosage forms, on practical measures of BE from which products can be developed. As more data on the pharmaceutical and clinical relevance of various techniques, as described in this review, become available, it is likely that a path to the demonstration of BE will become evident. In the meantime, debate on this topic will continue.